VIOLATION OF MAXIM OF CONVERSATION IN THE SERIAL COMICS ENTITLED DILBERT - Redi Pustaka (Universitas Katolik Widya Mandala Surabaya, 2015)
Abstract This writing discusses violation of maxims of conversation in the serial comics entitled Dilbert. The comics themselves are short and daily comics which present the conversation among the employees in a company. In addition, the events which happen in the comics were actually taken from Scott Adam’s personal experiences. The research focuses on the kinds of violation of maxim of conversation and the purpose of the violation. Generally, this research is included in descriptive study. In this research, the procedures done are collecting, classifying, and analyzing the data. The entire data of this research were taken from serial comics entitled Dilbert written by Scott Adam. Then, the unit of analysis of this research is the whole conversations which represent violation of maxim of conversation. Furthermore, total sampling was applied to obtain the required samples. Consequently, the researcher had to analyze the sample one by one. To analyze the data, the researcher used referential equivalent method to classify the kind of violated maxim of conversation and pragmatic equivalent method to reveal the purposes of it. Based on the analysis, the highest violation of maxim of conversation is in the violation of maxim of manner by 36 data. Furthermore, violation of maxim of quality is in the lowest position by 5 data only. Meanwhile, the writer discovers that representative dominates the purpose of the characters in violating the maxims of conversation by 37 amounts of data. Then, the smallest purpose is declarations by 5 samples. Keywords: pragmatics, maxim of conversation, violation, dan purpose of violation of maxim of conversation